Liquid Crystalline Polymers Volume 1-Structure and Chemistry - Thakur, Vijay Kumar; Kessler, Michael R. (Springer International Publishing : Imprint: Springer, 2016)
This book introduces anisotropic innovations in liquid crystalline polymers as well as new nanocomposite materials and testing techniques. The authors detail the newest discoveries of material properties, material types and phases, and material characterization.  This interdisciplinary work creates valuable links that strengthen the approach to the evolving field of liquid crystalline polymers/materials.